Hepatitis E infection in Odisha, India: A descriptive analysis - Shantanu K Kar; Bhagirathi Dwibedi; Vijayalaxmi V Mogasale; Jyotsnamayee Sabat; Vittal Mogasale; Thomas F Wierzba (Wolters Kluwer Medknow Publications, 2018)
Up to 25% of hepatitis E virus (HEV)-infected pregnant women in their third trimester die. Despite HEV being an important cause of viral hepatitis, no robust surveillance exists in India. We reviewed jaundice outbreaks records and hospital records from jaundiced individuals seeking treatment and linked those records to laboratory results (HEV immunoglobulin M enzyme-linked immunosorbent assay) for January 2012 to September 2013 in Odisha state. A total of 14 HEV confirmed outbreaks were identified, of which 33% of 139 jaundiced cases were HEV positive. There were two deaths. An additional 495 jaundiced cases were identified through hospital records, of which 18% were HEV positive. Among HEV-positive women (n = 35), 34% were of childbearing age. While one may not be able to generalize our results, this finding suggests HE is widespread in Odisha and may represent hidden disease burden in this region. The policymakers should monitor HEV infections in similar geographical areas, especially among population of childbearing age women to initiate evidence-based control measures.